Use of antimicrobials during the COVID-19 pandemic: A qualitative study among stakeholders in Nepal. - Binod Dhungel; Upendra Thapa Shrestha; Sanjib Adhikari; Nabaraj Adhikari; Alisha Bhattarai; Sunil Pokharel; Abhilasha Karkey; Direk Limmathurotsakul; Prakash Ghimire; Komal Raj Rijal; Phaik Yeong Cheah; Christopher Pell; et al. (Public Library of Science (PLoS), 2023)
The COVID-19 pandemic was a major public health threat and the pressure to find curative therapies was tremendous. Particularly in the early critical phase of the pandemic, a lot of empirical treatments, including antimicrobials, were recommended. Drawing on interviews with patients, clinicians and drug dispensers, this article explores the use of antimicrobials for the management of COVID-19 in Nepal. A total of 30 stakeholders (10 clinicians, 10 dispensers and 10 COVID-19 patients) were identified purposively and were approached for an interview. Clinicians and dispensers in three tertiary hospitals in Kathmandu assisted in the recruitment of COVID-19 patients who were undergoing follow-up at an out-patient department. Interviews were audio recorded, translated and transcribed into English, and were analyzed thematically. The respondents report that over-the-counter (OTC) use of antibiotics was widespread during the COVID-19 pandemic in Nepal. This was mostly rooted in patients' attempts to mitigate the potential severity of respiratory illnesses, and the fear of the stigmatization and social isolation linked to being identified as a COVID-19 patient. Patients who visited drug shops and physicians reportedly requested specific medicines including antibiotics. Clinicians reported uncertainty when treating COVID-19 cases that added pressure to prescribe antimicrobials. Respondents from all stakeholder groups recognized the dangers of excessive use of antimicrobials, with some referring to the development of resistance. The COVID-19 pandemic added pressure to prescribe, dispense and overuse antimicrobials, accentuating the pre-existing OTC use of antimicrobials. Infectious disease outbreaks and epidemics warrant special caution regarding the use of antimicrobials and specific policy response.